1969
DOI: 10.1099/0022-1317-4-4-513
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interferon in Replication of Virulent and Attenuated Strains of Measles Virus

Abstract: SUMMARYSmall concentrations of actinomycin D increased the yields of both virulent and attenuated strains of measles virus in cultures of the stable simian BSC-I cell line by as much as five-to tenfold. The EDMONSTON virulent strain of measles virus did not induce detectable levels of interferon in these cells but interferon was induced by the SCHW~u'Z vaccine (attenuated) strain of virus over a wide range of virus input. Actinomycin D suppressed the induction of interferon in BSC-I cells. Interferon produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1969
1969
2002
2002

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Ruiz-Gomez and Isaacs (1963a) studied a number of different viruses and reported that the more virulent ones induced the least amounts of interferon. Similar results were obtained for strains of Semliki Forest, measles and Japanese encephalitis viruses (Finter, 1964;Mirchamsy and Rapp, 1969;Rokutanda, 1969). Vilikk (1964), however, found that the amount of interferon produced in mice infected with Sindbis virus was directly related to virus multiplication and he concluded that interferon formation was more probably a secondary response to, rather than a determining factor in, virus replication.…”
supporting
confidence: 74%
“…Ruiz-Gomez and Isaacs (1963a) studied a number of different viruses and reported that the more virulent ones induced the least amounts of interferon. Similar results were obtained for strains of Semliki Forest, measles and Japanese encephalitis viruses (Finter, 1964;Mirchamsy and Rapp, 1969;Rokutanda, 1969). Vilikk (1964), however, found that the amount of interferon produced in mice infected with Sindbis virus was directly related to virus multiplication and he concluded that interferon formation was more probably a secondary response to, rather than a determining factor in, virus replication.…”
supporting
confidence: 74%
“…Several studies have shown that MV strains differ in their IFN-inducing properties, and it has been suggested that virulent MVs can inhibit the induction of type 1 IFN (see, for instance, Mirchamsy & Rapp, 1969 ;Naniche et al, 2000 ;Volckaert-Vervliet et al, 1978). Naniche et al (2000) recently reported that wild-type isolates, which had been isolated and passaged on lymphoid cells, were much weaker inducers of type 1 IFN than the Edmonston strain and the Edmonston-derived Moraten vaccine strain.…”
Section: Discussionmentioning
confidence: 99%
“…Table I Discussion. The effect of AD on yields of the RNA-containing arboviruses (7, 8), Newcastle disease virus ( 9 ) , and human measles virus (6) has been postulated to be the result of inhibition of induction of interferon. This idea correlates with our present data.…”
mentioning
confidence: 99%